Um estudo exploratório sobre os mecanismos que permitem a capilarização das lições aprendidas na organização: estudo de caso de empresas industriais brasileiras competitivas - Xanthopoylos, Stavros Panagiotis (2005)
Exploiting the organization's lessons learned is a relevant activity within knowledge management. Lessons learned are part of endemic knowledge instruments which originate from success or failure experience and are motivated during the deployment of tasks or phenomena observation in the activities or organizational processes, It can increase the individual's knowledge when shared or transformed into explicit knowledge which consequently contributes to enhance the organizational knowledge. Recent research and literature have shown that effective results from knowledge sharing and transferring are far beyond from what expected, especially in relation to returns on the high investments made in projects and information technology tools. The present work studies lessons learned in the organization through a perspective of knowledge transfer and sharing mechanisms in the context as how these can promote the dynamic management of lessons learned and thus bridging the result gap. The theoretical framework was developed based on learning cycles proposed by Stewhart and Kolb, for example, applied in continuous improvement processes in organizations. Furthermore, knowledge sharing and transfer models were studied, exploring a broad scope of relevant researchers, such as, Szulanski, Argyris and Dixon. The key success factors were analyzed and a list of relevant communication mechanisms was built, both for personal, face to face, and electronic ones, applicable to the study's scope. This theoretical framework served as a research protocol applied in a field case study in three Brazilian industrial enterprises, recognized as competitive, solid, successful, innovative and leading companies in their markets, among other attributes which contribute for the objectives of present study. Replication of the theoretical framework was sought, besides surveying the degree of 'capillarity' of the lessons learned in the organization through observation of the sufficiency and efficiency of the sharing and transfer mechanisms deployed. The 'capillarity' metaphor used in this context, refers to the extent of how the lessons learned reach every spot in the organization, increasing the potential use of the benefits carried by the knowledge held in them, creating possibilities for organizational improvement; a key role of knowledge management.